PELATIHAN KOMUNIKASI INTERPERSONAL BERBASIS KOMPETENSI UNTUK MENINGKATKAN KOMUNIKASI KERJA TIM KELOMPOK KADER POSYANDU - Lina Martina Sari; Amarina Ashar Ariyanto (Jurnal Ilmu dan Budaya, 2019)
The effectiveness of teamwork is the main key of the group performance, group cohesion, collective efficacy and member satisfaction (Aguado et al, 2014). Ineffective teamwork in a group occurs because of the lack of effective communication skills of members (Steven & Campions, 1994). The problem of ineffective teamwork due to lack of communication skills is experienced by one group of Posyandu cadres in East Jakarta. To improve teamwork communication the Posyandu cadre group, researchers conducted interpersonal communication training interventions. This intervention study is quantitative and qualitative field research with design, after and before with control design. The results of the statistical analysis showed an increase in the working communication of the Posyandu cadre team after attending interpersonal communication training. Based on observations and interviews related to teamwork communication, that are known to make formal communication, are able to communicate openly and supportively, listen more and respond positively to other cadres' opinions, increasingly recognize communicating non-verbally from other cadres, and reprimand also talk lightly when discussing.